Pengukuran Kepuasan Pelanggan dengan metode Customer Satisfaction Index dan Importance Performance Analysis (Studi pada Veroza Cake Bakery Kabupaten Dharmasraya Sumatera Barat) - Sampurno Wibowo; Muhammad Iqbal (Journal of Management and Bussines (JOMB), 2024)
This research aims to measure customer satisfaction as a basis for effective policy making, focusing on the 4P dimensions (Product, Price, Place, Promotion). The research method uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) to evaluate the current level of customer satisfaction. The research results show a CSI value of 78.75%, indicating that Veroza Cake & Bakery MSE consumers are generally satisfied with the services provided. The IPA analysis identified three attributes as top priorities (quadrant I), seven attributes whose achievements need to be maintained (quadrant II), two attributes with low priority (quadrant III), and three attributes that are classified as excessive (quadrant IV). In conclusion, there is a need to improve services, especially on attributes that have a low level of satisfaction but have a high level of importance, especially in the promotion dimension. This research provides a basis for the company to implement more effective policies to increase customer satisfaction and ensure the operational continuity of MSE Veroza Cake & Bakery in a competitive market. Keywords: Customer Satisfaction Index, Importance Performance Analysis, Customer Satisfaction